Refining anti‐inflammatory therapy strategies for bronchopulmonary dysplasia. Issue 6 (13th December 2016) - Rudloff, Ina; Cho, Steven X.; Bui, Christine B.; McLean, Catriona; Veldman, Alex; Berger, Philip J.; Nold, Marcel F.; Nold‐Petry, Claudia A.
Abstract: Bronchopulmonary dysplasia (BPD) is a severe lung disease of preterm infants, which is characterized by fewer, enlarged alveoli and increased inflammation. BPD has grave consequences for affected infants, but no effective and safe therapy exists. We previously showed that prophylactic treatment with interleukin‐1 receptor antagonist (IL‐1Ra) prevents murine BPD induced by perinatal inflammation and hyperoxia. Here, we used the same BPD model to assess whether an alternative anti‐inflammatory agent, protein C (PC), is as effective as IL‐1Ra against BPD. We also tested whether delayed administration or a higher dose of IL‐1Ra affects its ability to ameliorate BPD and investigated aspects of drug safety. Pups were reared in room air (21% O2 ) or hyperoxia (65% or 85% O2 ) and received daily injections with vehicle, 1200 IU/kg PC, 10 mg/kg IL‐1Ra (early or late onset) or 100 mg/kg IL‐1Ra. After 3 or 28 days, lung and brain histology were assessed and pulmonary cytokines were analysed using ELISA and cytokine arrays. We found that PC only moderately reduced the severe impact of BPD on lung structure (e.g. 18% increased alveolar number by PC versus 34% by IL‐1Ra); however, PC significantly reduced IL‐1β, IL‐1Ra, IL‐6 and macrophage inflammatory protein (MIP)‐2 by up to 89%. IL‐1Ra at 10 mg/kg prevented BPD more effectively than 100 mg/kg IL‐1Ra, but only if treatment commenced at day 1 of life. We conclude that prophylactic low‐dose IL‐1Ra and PC ameliorate BPD and have potential as the first remedy for one of the most devastating diseases preterm babies face.